Influence of geometric and environmental parameters on air-cooled steam condenser performance - Joubert, Retief (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2010.